Advanced introduction to international sales law - Gillette, Clayton P (Edward Elgar, 2016)
"Providing a concise overview of the basic doctrines underlying the UN Convention on Contracts for the International Sale of Goods (CISG), Clayton Gillette explores their ambiguities and thus considers the extent to which uniform international commercial law is possible, as well as appraising the extent to which the doctrines in the UN Convention reflect those that commercial parties would prefer. With its compelling combination of doctrine and theory, this book makes an ideal companion for students and legal scholars alike. Key features include: concise and compact overview of the CISG, includes contemporary developments, provides a theoretical basis for evaluating international sales law, considers perspectives of economic analysis of law"--Cover.